2017
DOI: 10.2135/cropsci2016.08.0695
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Simple Sequence Repeat Markers Associated with Inheritance of Sweetpotato Virus Disease Resistance in Sweetpotato

Abstract: Sweetpotato virus disease (SPVD), a complex of Sweet potato chlorotic stunt virus (SPCSV; Crinivirus) and Sweet potato feathery mottle virus (SPFMV; Potyvirus) causes high yield losses in sub‐Saharan Africa (SSA). The development of resistant cultivars to SPVD has been limited by the complex sweetpotato [Ipomoea batatas (L.) Lam. var. batatas] genetics and high levels of mutations in the causal viruses. The objectives of this study were to understand the inheritance of SPVD resistance and identify simple‐seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…A recent map was developed from a selfing population and used only single-dose SNPs, resulting in higher marker saturation in comparison to the previous maps (Shirasawa et al 2017), though the map was still not integrated. In some of these cases, QTL mapping analyses were performed for several traits, related mostly to quality (Cervantes-Flores et al 2011;Zhao et al 2013;Yu et al 2014;Kim et al 2017) and resistance to biotic stresses (Cervantes-Flores et al 2008b;Yada et al 2017a). For yield-related traits, only two studies have been reported to date (Chang et al 2009;Li et al 2014).…”
Section: Qtl Mapping For Yield Traits In Sweetpotatomentioning
confidence: 99%
“…A recent map was developed from a selfing population and used only single-dose SNPs, resulting in higher marker saturation in comparison to the previous maps (Shirasawa et al 2017), though the map was still not integrated. In some of these cases, QTL mapping analyses were performed for several traits, related mostly to quality (Cervantes-Flores et al 2011;Zhao et al 2013;Yu et al 2014;Kim et al 2017) and resistance to biotic stresses (Cervantes-Flores et al 2008b;Yada et al 2017a). For yield-related traits, only two studies have been reported to date (Chang et al 2009;Li et al 2014).…”
Section: Qtl Mapping For Yield Traits In Sweetpotatomentioning
confidence: 99%
“…Field screening is problematic because vector populations fluctuate over seasons and years (Aritua et al, 1998;Clark et al, 2012) and roots are available only after completing a first seedling generation. Typically, large (50,000-100,000) populations of F 1 seedlings require testing for several seasons for several years to identify agronomically superior genotypes with true SPVD resistance (Mwanga et al, 2013;Yada et al, 2017b). Initially, plants may escape infection, taking three or more years to show SPVD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the detection of microsatellites (SSR markers) within the DNA coding regions of the defense genes indicates an improvement in understanding of defense genes and virus resistance compared with previous knowledge (Mwanga et al, 2002;Yada et al, 2017). It is important to note that the sweet potato SSRs currently known (Parado, 2010;Wang et al, 2011) are randomly located within the genome and tend to be difficult to develop or study without the use of sophisticated equipment (Schafleitner et al, 2010;Wang et al 2011); however, the method used in the present is inexpensive and targeted to specific genes and chromosomes.…”
Section: Markermentioning
confidence: 76%